Modelagem computacional para análise do inbreeding academico - Barros, Roni Storti de (2024)
The present study presents an investigation into the topic of Academic Inbreeding. Supported by Berelson's study (1961) on this concept (recruitment of academics by the same institution in which the doctorate was carried out), the hiring as teachers of candidates who have already had some academic training at the institution where they work. The main objective of the investigation was to design, develop and evaluate system dynamics model(s) capable of supporting the decision-making process regarding the hiring of teachers with different levels of Inbreeding. The levels used were based on the study by Horta (2013). However, instead of studying only the candidate's last degree, their links since graduation, followed by master's and doctorate were analyzed. In this way, the classifications “No inbreeding” were used (for those who had no previous academic ties with the institution investigated) and inbreeding levels A to C (according to the number of ties with the institution they work for). As a method, Systems Dynamics was used, which allowed evaluating the performance of the teachers in the sample through time, development, simulation and evaluation of models; as well as mapping cooperation networks in the academic production of teachers. As a result, it was found that the scenario of teachers “Without inbreeding” (teachers with no previous academic ties at the educational institution evaluated) presented better performance, while teachers classified as “inbreeding B” (teachers with two previous academic ties at the institution) had the worst performance - corroborating studies on the subject. With the support of network mapping, it was possible to visually understand this reality, since “No inbreeding” professors have a greater number of branches in their networks, as well as greater relationships with other institutions (including institutions abroad). Comparing teachers from private and public institutions, it is clear that teachers from private institutions achieved better results when measuring scientific efficiency and productivity, such as publications in journals. Finally, it was found that inbreeding is more common in the development/creation phases of departments or educational institutions.